FAKTOR SUKU DALAM POLA KOMUNIKASI, PENYESUAIAN SUAMI ISTRI, DAN KEHARMONISAN KELUARGA - Septiana, Venti Sanditya; Krisnatuti, Diah; Simanjuntak, Megawati (Jurnal Ilmu Keluarga dan Konsumen, 2014)
The aim of the study was to analyze communication pattern, marital adjustment, and family harmony among two types of ethnic family. This study involved 30 families with husband and wife who were from the same ethnic and 30 families from the different one. The data was collected by interviewing husband and wife and used questionnaires. Communication pattern was measured by how couples communicate each other, while marital adjustment was measured by four aspects that were adjustment with couple, sexual adjustment, financial adjustment, and adjustment to the couple’s family. Family harmony was measured by satisfaction level of the respondent. Result showed that communication pattern of both families who were from the same and different ethnic categorized as high while marital adjustment and family harmony were categorized as moderate. There were no differences on communication pattern, marital adjustment, and family harmony between same and different ethnic families (p>0,05). However, wife’s age, marriage age, and family income had significant correlation with family harmony in different ethnic families. Additionally, there was a significant positive relationship between communication pattern and marital adjustment with family harmony in both groups of family. In general, factors that affected the family harmony were communication pattern and marital adjustment.